THE CRIMINAL LIABILITY OF THE OWNERS OF INDUSTERIES FOR ENVIRONMENTAL CRIMES "COMPARATIVE STUDY" - Ali Hamzah Jebur (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Industrial pollution is one of the most important issues raised at the local and international level, due to the great risks it causes to the ecosystem and the health of society alike. Hence, countries found the issue presented in international organizations to reduce the emission of harmful gases and work to reduce the waste dumped from industrial projects, while they turned Internal legislation indicates the need to intervene to adopt punitive texts to confront this type of environmental pollutants, while preserving two important factors, namely preserving the integrity of the environment and taking into account the preservation of industrial policy in countries, given that it is a tool of economic and social policy in the country, hence the importance of Environment and industry alike found the idea of ​​holding the owners of industrial projects that violate the environment accountable, and in this research we delve into the issue of the criminal liability of the owners of industrial enterprises for environmental pollution crimes, a "comparative study", focusing on the adequacy of the punitive texts to confront such crimes, as we present this topic on Like two topics preceded by an introduction, in the first section we deal with the concept of the owners of industrial enterprises, while the second topic studies examples of crimes that cause Environmental pollution, then the research ends with a conclusion that includes the most prominent conclusions and proposals.